Selective elimination of neuroblastoma cells by synergistic effect of Akt kinase inhibitor and tetrathiomolybdate - Navrátilová, Jarmila; Karasová, Martina; Kohutková Lánová, Martina; Jiráková, Ludmila; Budková, Zuzana; Pacherník, Jiří; Šmarda, Jan; Beneš, Petr (Journal of cellular and molecular medicine, 2017)
Neuroblastoma is the most common extracranial solid tumour of infancy. Pathological activation of glucose consumption, glycolysis and glycolysis-activating Akt kinase occur frequently in neuroblastoma cells, and these changes correlate with poor prognosis of patients. Therefore, several inhibitors of glucose utilization and the Akt kinase activity are in preclinical trials as potential anti-cancer drugs. However, metabolic plasticity of cancer cells might undermine efficacy of this approach. In this work, we identified oxidative phosphorylation as compensatory mechanism preserving viability of neuroblastoma cells with inhibited glucose uptake/Akt kinase. It was oxidative phosphorylation that maintained intracellular level of ATP and proliferative capacity of these cells. The oxidative phosphorylation inhibitors (rotenone, tetrathiomolybdate) synergized with inhibitor of the Akt kinase/glucose uptake in down-regulation of both viability of neuroblastoma cells and clonogenic potential of cells forming neuroblastoma spheroids. Interestingly, tetrathiomolybdate acted as highly specific inhibitor of oxygen consumption and activator of lactate production in neuroblastoma cells, but not in normal fibroblasts and neuronal cells. Moreover, the reducing effect of tetrathiomolybdate on cell viability and the level of ATP in the cells with inhibited Akt kinase/glucose uptake was also selective for neuroblastoma cells. Therefore, efficient elimination of neuroblastoma cells requires inhibition of both glucose uptake/Akt kinase and oxidative phosphorylation activities. The use of tetrathiomolybdate as a mitochondrial inhibitor contributes to selectivity of this combined treatment, preferentially targeting neuroblastoma cells.
Keywords: Animals; Proto-Oncogene Proteins c-akt; inhibitory proteinkinas; Cell Line, Tumor; Mitochondria; molybden; buněčné dýchání; Fibroblasts; Lactic Acid; kyselina mléčná; nádorové buněčné linie; Oxidative Phosphorylation; Oxygen Consumption; lidé; neurony; adenosintrifosfát; fibroblasty; Molybdenum; Phosphorylation; mitochondrie; protoonkogenní proteiny c-akt; Neurons; Down-Regulation; oxidativní fosforylace; fosforylace; Adenosine Triphosphate; Protein Kinase Inhibitors; glukosa; Glucose; Cell Respiration; Neuroblastoma; down regulace; neuroblastom; zvířata; Mice, Inbred C57BL; spotřeba kyslíku; myši inbrední C57BL; Humans